Italian horror cinema - Baschiera, Stefano 1977-; Hunter, Russ 1977- (Edinburgh University Press, 2016)
Covering the fundamental aspects of Italian horror cinema and written by experts in the field, this book engages with the genres transnational form of production and distribution, critical reception, relationship between horror and Italian art cinema, use of sound and legacy. Case studies include 'The Girl Who Knew Too Much' (1963), 'Zombie 2' (1973), 'Deep Red' (1975), 'The Stendhal Syndrome' (1996), 'The Last House in the Woods' (2006) and 'Bay of Blood' (1971)
Description based on print version record
Keywords: Geschichte; Horror films; Motion pictures, Italian; Horrorfilm; Italien; Aufsatzsammlung